2011
DOI: 10.1080/00324728.2011.604730
|View full text |Cite
|
Sign up to set email alerts
|

Trends in late-life disability in Taiwan, 1989–2007: The roles of education, environment, and technology

Abstract: This analysis offers the first strong evidence of trends in late-life disability in an emerging economy. Consistent measures of limitations in seeing, hearing, physical functions, instrumental activities of daily living (IADLs), and activities of daily living (ADLs) were available for three to six survey waves, depending on the outcome, from 1989 to 2007 for the population of Taiwan aged 65 and older. Limitations in seeing, hearing, and IADLs declined substantially, but trends were mixed for physical functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 42 publications
(48 reference statements)
4
43
1
Order By: Relevance
“…For example, in the United States, IADL disability steadily declined before the early 2000s despite relatively stable levels of ADL functioning in older Americans (Freedman et al 2004(Freedman et al , 2013Lin et al 2012). A similar pattern was found in Taiwan from 1989 to 2007 (Martin et al 2011;Ofstedal et al 2007). Feng and Zeng (2014) found that the decline in IADL disability was more pronounced than the decline in ADL disability among older adults in China from 2002 to 2008 (Feng and Zeng 2014).…”
Section: Empirical Evidence Of Overall Trends In Disabilitysupporting
confidence: 52%
See 3 more Smart Citations
“…For example, in the United States, IADL disability steadily declined before the early 2000s despite relatively stable levels of ADL functioning in older Americans (Freedman et al 2004(Freedman et al , 2013Lin et al 2012). A similar pattern was found in Taiwan from 1989 to 2007 (Martin et al 2011;Ofstedal et al 2007). Feng and Zeng (2014) found that the decline in IADL disability was more pronounced than the decline in ADL disability among older adults in China from 2002 to 2008 (Feng and Zeng 2014).…”
Section: Empirical Evidence Of Overall Trends In Disabilitysupporting
confidence: 52%
“…Any change in one item or component of disability may not necessarily indicate corresponding change in another (Crimmins 1996;Martin et al 2011). For example, declines in ADL functioning among older community-dwelling Americans were primarily attributable to declines in mild to moderate levels of functionality; reductions in the prevalence of more severe ADL disability appeared to have been smaller (Freedman et al 2004).…”
Section: Empirical Evidence Of Overall Trends In Disabilitymentioning
confidence: 92%
See 2 more Smart Citations
“…As mentioned in previous research, Asian countries have not reported evidence for compression of morbidity [28] and Ku, Liu and Wen [29] carried out a study in Taiwan found that the trend in having at least one of the six ADL limitations among communitydwelling elderly people increased mildly in the past decade. The use of community services also increased over this period, not because of widespread substitution of community care for nursing home care, but because of increased use among those in the community [30].…”
Section: Mental Health Outcomes -Cognition and Depressionmentioning
confidence: 99%